2014
DOI: 10.1242/dmm.014050
|View full text |Cite
|
Sign up to set email alerts
|

Loss of lysosomal protein NCU-G1 results in spontaneous liver fibrosis with accumulation of lipofuscin and iron in Kupffer cells

Abstract: Human kidney predominant protein, NCU-G1, is a highly conserved protein with an unknown biological function. Initially described as a nuclear protein, it was later shown to be a bona fide lysosomal integral membrane protein. To gain insight into the physiological function of NCU-G1, mice with no detectable expression of this gene were created using a gene-trap strategy, and Ncu-g1gt/gt mice were successfully characterized. Lysosomal disorders are mainly caused by lack of or malfunctioning of proteins in the en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(43 citation statements)
references
References 81 publications
(129 reference statements)
3
40
0
Order By: Relevance
“…Abnormal accumulation of lipids in the liver is a known consequence of dysregulation of metabolism [ 41 ]. However, in our initial report, histological analysis failed to reveal obvious steatosis in Glmp gt/gt liver [ 5 ]. Here, using a biochemical approach, we showed that Glmp gt/gt mice accumulated slightly more liver TAG than WT animals.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Abnormal accumulation of lipids in the liver is a known consequence of dysregulation of metabolism [ 41 ]. However, in our initial report, histological analysis failed to reveal obvious steatosis in Glmp gt/gt liver [ 5 ]. Here, using a biochemical approach, we showed that Glmp gt/gt mice accumulated slightly more liver TAG than WT animals.…”
Section: Discussionmentioning
confidence: 98%
“…We have recently established that the Glmp gt/gt mice suffer from a mild chronic liver injury, as indicated by the modest increase in serum transaminase levels. However, by the age of 6 months, the sustained liver injury led to a well-established fibrosis with increased inflammation and oxidative stress [ 5 ], conditions known to disturb the liver's capacity for regulating glucose, lipid and protein homeostasis [ 18 ]. As the liver is an important organ for glucose homeostasis [ 27 ], the small decrease in resting blood glucose may be caused by increased glucose flow to the liver.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations